ANALYSIS OF THE IMPACT OF THE GREEN ECONOMY ON SUSTAINABLE AGRICULTURAL DEVELOPMENT IN IRAQ FOR THE PERIOD (2003-2022) - Sfayyih, Lina Kadhim; Shukr, Ali. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The research aims to study the impact of the green economy on achieving sustainable agricultural development in Iraq for the period (2003-2022). The research used quantitative methods in analyzing GDP, green GDP, investment allocations for the agricultural sector, environmental allocations, cultivated areas and water imports of the Tigris and Euphrates rivers to distinguish the impact of these variables on agricultural GDP. The parameters were estimated using the Autoregressive Distributed Lag-ARDL framework. The results found that each of the green GDP, investment allocations, and environmental allocations came positive and consistent with the logic of the economic theory, while cultivated areas came positive but not significant. Rivers water flow had a negative signal due to the significant decline during the study period. The research found that the green GDP has the largest effect in agricultural GDP, and its impact is clear in advancing the development process. The research recommended the need to follow scientific methods and modern methods to reduce toxic and greenhouse gas emissions, which greatly affect pollution and agricultural production